Pharmacy Practice Scenario and Job Satisfaction among Nepalese Pharmacists - Khanal, Dharma Prasad; Dhungana, Bishwo Raj; Kadyat, Naresh (Journal of Karnali Academy of Health Sciences, 2019)
Background:This is an effort just snapshot the pharmacy practice scenario in Nepal. Job satisfaction is a very important contributing factor for person’s productivity and motivation. Pharmacists are the key players of the health care system. The main objective find out the present scenario of pharmacy practice and job satisfaction of Nepalese pharmacists. We start our approach from the demographic information, choice and selection of the pharmacy education, study site, practicing site, duration of work, expected and real salary of practicing pharmacists. Methods:A practice scenario and job satisfaction related questionnaires were developed and pilot test was done with ten pharmacy practitioners who were practicing from more than ten years in Nepal for reliability. Minor modification on questionnaires was done after pilot testing. Ethical clearance was taken from the MMIHS –IRC. Results:Male pharmacists are dominating to female. The satisfaction level of Nepalese pharmacist was found to be 73.60%. Similarly, around 73.10% of pharmacists were satisfied with nature of work and 71.60% of pharmacists were satisfied with the time duration of work whereas nearly half of the pharmacists were unsatisfied with their income and pay scale. Conclusion: Till date pharmacist is not the permanent member of health care system in Nepal. 70 % pharmacists are highly productive stage of between ages 20-30 years. The inherent interest in the pharmacy profession found among Nepalese pharmacists is an optimistic and policy-makers could develop, modifying national health policy for the implementation of pharmaceutical service as an integral part of national health care system of the country for the benefit of the public health as a whole. The Government and other authorities have to consider for a universal, multifaceted measure of satisfaction not merely the salary benefits.